ANALISIS KESULITAN PADA PESERTA DIDIK DI SMP 1 PASUNDAN CIMAHI DALAM MENYELESAIKAN SOAL MATERI PERSAMAAN GARIS LURUS - Kurnia Sandra Ningsih; Gida Kadarisma (IKIP Siliwangi, 2023)
This study aims to analyze the difficulties faced by Grade VIII junior high school students in straight line equations. The subjects of this study were 20 students in class VIII A at SMP Pasundan 2 Cimahi. The data used in this study is in the form of a test instrument, namely the form of 5 description questions using 5 indicators of achievement in straight line equation material. The results of this study obtained conclusions about the analysis of students' difficulties in solving math problems in straight line equation material based on indicators of competency achievement students have difficulty determining the formula used, determining the concept used in solving straight line equation problems so that students do not complete the answers properly and correctly. From the results of the study it can be concluded that the results of the analysis of students' difficulties in solving straight line equations material questions are still in the high category as seen from the low scores of students and the difficulties students face in solving straight line equations problems so that it is necessary to increase understanding of the concept of straight line equations material in learners.